Endogenous productivity and scale economies. a verdoorn law application in the Portuguese regions - Vitor Jo\~ao Pereira Martinho (European Regional Science Association (ERSA), 2004)
In agreement with the Verdoorn law the growth rate of the work productivity is endogenous and it depends on the growth rate of the industrial product. This relationship (with the coefficient of Verdoorn inferior to the unit) evidences substantial scale economies that are in the base of economic growth models with circular and cumulative causes. With this work we intend to test the Verdoorn Law, with the alternatives specifications of Kaldor (1966), for the 5 Portuguese regions (NUTs II) in the period from 1986 to 1994 and for the 28 Portuguese NUTs III in the period from 1995 to 1999. We intend, like this, to analyse the existence of increasing returns to scale that characterize the polarization processes with circular and cumulative causes and can explain the processes of regional divergence. A little to the similarity of what has been effectuated in other works associated to the New Economic Geography, in that they try to analyse the existence of increasing returns to scale and agglomeration processes with circular and cumulative causes. Although the theoretical base is different, in other words, macro-economic in the Keynesian developments associated to the Verdoorn Law and micro-economic in the New Economic Geography. We intend to test, still in this work, the alternative interpretation of Rowthorn (1975) of the Verdoorn Law for the same regions and periods. The results of this work will be complemented with estimates of these relationships for others economic sectors besides the industry (primary sector and services), for each one of the manufactured industries to operate in the Portuguese regions and for the total of the economy of each region. We did estimates for the others economic sectors (primary sector and services), because the modern economies could have more than a sector subject to increasing returns, especially in some services activities. The estimates for the total of the regional economy intend to verify the scale economies at regional level.
Keywords: 330